The effect of 5555 strategy on reading comprehension among 4th preparatory students (Journal Of Educational and Psychological Researches, 2018)
The effect of 5555 strategy on reading comprehension among 4th preparatory students Assist. Prof. Dr. Hassan Khilbas Hammadi College of Education Ibn Rushd – The University of Baghdad Assistant Lecturer. Waleed Khaled Talib Directorate – General For Education Province Of AL - Anbar The purpose of study is to identify the effect of 5555 strategy on reading comprehension among 4th preparatory students. To do this, null hypothesis was postulated. The author hypothesize that there is no a statistically significant difference at (0.05) level between experimental group's scores who study reading comprehension subject following the 5555 strategy and control group's scores who study the same subject following the traditional method in reading comprehension. The study comprised (66) student, whereby the experimental group was made up of (33) students, while the control group made up of (33) student were chosen from Al-Ramadi developed school for the academic year (2016-2017). The authors prepared a scale to measure the reading comprehension which consist of 4 question: question one composed of (18) item; question two made up of two paragraphs where asked to reorganize the words; question three consisted of ten matching items; and the question 4 contained ten items which asked to complete them. The result revealed that the experimental group has a statistically significant difference at (0.05) level.